The "silent guardians" in the fight against corruption - Tudjarovska Gjorgjievska, Emilija (Central European Public Administration Review, 2020)
Impartial public administration is a key gatekeeper against corruptive practices and the necessary condition for the process of democratisation. Yet, in the case of North Macedonia, there is an ongoing challenge in addressing the problem of politicisation of public administration. On one hand, the ombudsman holds the normative position to safeguard citizens in front of state administration bodies, to act upon the impar' tiality biases or other deviances of norms, and to annually report to the National Parliament. On the other hand, the parliament should be able to hold executives and institutions accountable for their actions and to act upon the ombudsman's recommendations. However, there is a limited understanding of the role that these two institutions can play in an effective fight against corruption as part of the democratisation processes. The purpose of the article is to examine the institutional gaps where the opportunities for corruption and social traps are encouraged. Based on theoretical, empirical as well as comparative observations, within single case method analysis, this article aims to examine the compliance of the theoretical fingerprints with the actual practice and provide a different angle on the institutional opportunities for social traps, in the context of unconsolidated democracies. The findings show that there is a causality between the institutional' silent guardian' of the citizens and the prevlence of corruption. It also encourages further discussion on the factors that undermine the positions of the ombudsman and the parliament to take active engagement in rooting out the corruption from societies.
Keywords: anti-corruption; democratisation; impartiality; north Macedonia; ombudsman; parliament